Biased expectations and labor market outcomes: Evidence from German survey data and implications for the East-West wage gap - Almut Balleer; Georg Duernecker; Susanne Forstner; Johannes Goensch (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
We measure individual bias in labor market expectations in German survey data and find that workers on average significantly overestimate their individual probabilities to separate from their job when employed as well to find a job when unemployed. These biases vary significantly between population groups. Most notably, East Germans are significantly more pessimistic than West Germans. We find a significantly negative relationship between the pessimistic bias in job separation expectations and wages, and a significantly positive relationship between optimistic bias in job finding expectations and reservation incomes. We interpret and quantify the effects of (such) expectation biases on the labor market equilibrium in a search and matching model of the labor market. Removing the biases could substantially increase wages and expected lifetime income in East Germany. The difference in biases in labor market expectations explains part of the East-West German wage gap. – – Diese Studie misst individuelle Verzerrungen von Arbeitsmarkterwartungen auf Basis deutscher Umfragedaten und stellt fest, dass beschäftige Arbeitnehmer ihre individuelle Wahrscheinlichkeit, den Arbeitsplatz zu verlieren, signifikant überschätzen. Ebenso überschätzen arbeitslose Arbeitnehmer ihre individuelle Wahrscheinlichkeit, einen Arbeitsplatz zu finden, signifikant. Diese Verzerrungen variieren erheblich zwischen Bevölkerungsgruppen, so sind z.B. ostdeutsche Arbeitnehmer deutlich pessimistischer als westdeutsche Arbeitnehmer. Die Studie dokumentiert einen signifikant negativen Zusammenhang zwischen der pessimistischen Erwartungshaltung beim Arbeitsplatzverlust und Löhnen sowie einen signifikant positiven Zusammenhang zwischen der optimistischen Erwartungshaltung bei der Arbeitssuche und dem Reservationseinkommen. Wir interpretieren und quantifizieren die Auswirkungen von Erwartungsfehlern auf das Arbeitsmarktgleichgewicht in einem Such- und Matching-Modell des Arbeitsmarktes. Eine Beseitigung der Verzerrungen könnte Löhne sowie das erwartete Lebenseinkommen in Ostdeutschland deutlich erhöhen. Der Unterschied in den Verzerrungen der Arbeitsmarkterwartungen erklärt einen Teil des Ost-West-Lohngefälles in Deutschland.
Keywords: E24; J31; D84; 330; Labor market risk; biased beliefs; wages; reservation wages